2022
DOI: 10.3390/ma15217856
|View full text |Cite
|
Sign up to set email alerts
|

Supercapacitor Properties of rGO-TiO2 Nanocomposite in Two-component Acidic Electrolyte

Abstract: The electrochemical properties of the highly porous reduced graphene oxide/titanium dioxide (rGO/TiO2) nanocomposite were studied to estimate the possibility of using it as a supercapacitor electrode. Granular aerogel rGO/TiO2 was used as an initial material for the first time of manufacturing the electrode. For the aerogel synthesis, industrial TiO2 Hombikat UV100 with a high specific surface area and anatase structure was used, and the aerogel was carried out with hydrazine vapor. Porous structure and hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It has been reported that ceramic particles play a critically vital role in various types of electrolytes [43,44]. In polymer electrolytes, adding ceramic particles such as SiO 2 [45,46], Al 2 O 3 [47], TiO 2 [48,49], and AlSi [50] can enhance ionic conductivity and prevent crystallization. Here we illustrate this process with plasmonic conductors in a fuel cell.…”
Section: Shear Thickening Electrolytementioning
confidence: 99%
“…It has been reported that ceramic particles play a critically vital role in various types of electrolytes [43,44]. In polymer electrolytes, adding ceramic particles such as SiO 2 [45,46], Al 2 O 3 [47], TiO 2 [48,49], and AlSi [50] can enhance ionic conductivity and prevent crystallization. Here we illustrate this process with plasmonic conductors in a fuel cell.…”
Section: Shear Thickening Electrolytementioning
confidence: 99%
“…Thus, good electrically conductive materials with a high surface area are desired to achieve high capacitance values of EDLCs. In this respect, carbon-based materials with varying morphologies, such as nanosheets, nanotubes, and fibers, have been comprehensively investigated for EDLCs [ 13 , 14 , 15 , 16 , 17 ]. On the other hand, capacitance generation in pseudocapacitors are based on reversible Faradaic processes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tin oxide decorated rGO, reported by Mao et al, is one of the earliest such materials, where the sensor showed decent activity in sensing an oxidizing gas (NO 2 ) but its response was lower than that of rGO for a reducing gas such as NH 3 . 39 Coupling r-GO with TiO 2 has been a productive strategy in various applications such as photocatalysis where the sp 2 hybridized sheets act as both an electron receptor and electron transporter, thus preventing excessive recombination of photogenerated charge carriers; 33,[40][41][42] heavy ion removal where the wrinkled and squiggled sheets create efficient contact of the metal oxide nanoparticles along with preventing their agglomeration, thus enhancing their activity; 43 nitrogen fixation to NH 3 where the TiO 2 -rGO hybrid nanocomposite has a lower charge transfer resistance and faster kinetics during the electrocatalysis reaction; electrochemical sensing of ions such as nitrite 44 and hormone ingredients such as epinephrine; 45 high voltage supercapacitors; [46][47][48] antimicrobial and self-cleaning coatings of textile materials; 49 dye-sensitized solar cells where applying r-GO as an interfacial layer between the substrate and TiO 2 resulted in enhanced charge transfer and reduced carrier recombination; 50 water splitting reaction; 51 binders in cement where TiO 2 helps in the dispersibility of r-GO, 52 etc.…”
Section: Introductionmentioning
confidence: 99%